Community-engaged research in translational science: Innovations to improve health in Appalachia. Issue 1 (7th October 2021) - Rhodes, Scott D.; Ballard, Parissa J.; Moore, Keena R.; Klein, Karen; Randall, Isaiah; Lischke, Michael; Vissman, Aaron T.; Lengerich, Eugene J.; Daniel, Stephanie S.; Skelton, Joseph A.
Abstract: Health disparities between Appalachia and the rest of the country are widening. To address this, the Appalachian Translational Research Network (ATRN) organizes an annual ATRN Health Summit. The most recent Summit was held online September 22–23, 2020, and hosted by Wake Forest Clinical and Translational Science Institute in partnership with the Northwest Area Health Education Center. The Summit, titled "Community-Engaged Research in Translational Science: Innovations to Improve Health in Appalachia, " brought together a diverse group of 141 stakeholders from communities, academic institutions, and the National Center for Advancing Translational Science (NCATS) to highlight current research, identify innovative approaches to translational science and community-engaged research, develop cross-regional research partnerships, and establish and disseminate priorities for future Appalachian-focused research. The Summit included three plenary presentations and 39 presentations within 12 concurrent breakout sessions. Here, we describe the Summit planning process and implementation, highlight some of the research presented, and outline nine emergent themes to guide future Appalachian-focused research.